PENERAPAN MODEL PEMBELAJARAN THINK,WRITE,AND TALK DALAM MENINGKATAKAN KUALITAS PEMBELAJARAN KEWIRAUSAHAAN - Henny Zurika (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
This study aims to improve students' activity and learning outcomes through the the application of thinking,write,and talk learning models as an effort to improve the quality of learning in entrepreneurship couses.